Research software in cochlear duct length estimation, Greenwood frequency mapping and CI electrode array length simulation - Anandhan Dhanasingh (KeAi Communications Co., Ltd., 2021)
Background and objective: The size of the cochlea varies a lot among the human population bringing the necessity for electrode arrays to be available in various lengths irrespective of the cochlear implant (CI) brand. This research software helps in the estimation of the patient's cochlear duct length (CDL) which is then used for the simulation of the correct length electrode array matching the patient's cochlear size and as well in getting the patient specific cochlear frequency map. Methods: Visual Studio Express 2012 for Windows Desktop is used in the architecture of this research software. The basal turn diameter of the cochlea (“A” value) needs to be measured from the pre-operative computed tomography (CT) image of the patient's temporal bone. This “A” will be taken as the input for the CDL equations proposed by Alexiades et al for estimating the CDL along the basilar membrane for various insertion depths. Greenwood's equation is then used in combination with the CDL for the full length of the cochlea in getting the patient specific frequency map. Results: The research software with the help of the “A” value as input, with few button clicks, gives the patient specific CDL for various insertion depths and the Greenwood's frequency map. The users have the choice to select any electrode array of their choice and place it under the frequency map to see how good it fits to that particular patient's cochlea. Also, given the possibility to drag and move the electrode array picture to mimic the post-operative actual electrode insertion depth. Conclusions: This research software simplifies the overall process of CDL estimation and in getting the patient specific cochlear frequency map. The clinicians get the chance to simulate placing the various electrode array lengths in patient cochlea in identifying the best fit electrode. This could help in pushing the CI field into the concept of individualized CI electrode array solution that ultimately benefits the patients.